2005
DOI: 10.1177/1468794105056921
|View full text |Cite
|
Sign up to set email alerts
|

Multiple methods in qualitative research with children: more insight or just more?

Abstract: This article explores the research implications of using multi-methods within a broad qualitative approach by drawing on the experience of conducting two childhood obesity-focused qualitative studies of Australian children’s perceptions and experiences of place, space and physical activity. Children described and depicted their physical activities and experiences: in focus group interviews, by mapping their local, social and recreational spaces and by photographing their meaningful places, spaces and activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
409
0
29

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 575 publications
(457 citation statements)
references
References 71 publications
3
409
0
29
Order By: Relevance
“…Children were given 20 minutes to complete the drawing (Darbyshire, 2005). After completing the drawings, children were gathered in focus groups supported by the use of a script, following different levels of the sociological model, (Table 2) and the personal drawings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children were given 20 minutes to complete the drawing (Darbyshire, 2005). After completing the drawings, children were gathered in focus groups supported by the use of a script, following different levels of the sociological model, (Table 2) and the personal drawings.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, other studies using qualitative approaches have primarily focused on conceptualizations (related to potential factors that influences physical activity) from an adult perspective (i.e., parents and teachers) rather than a child’s (Darbyshire, 2005). …”
mentioning
confidence: 99%
“…We also decided on this first day that we would need to find out where we would access the young people we want to speak to, and this was done through a mapping exercise. Research has shown that using mapping exercises has proven to be effective in groups with children as young as four years old in relation to their perceptions of their environment (Darbyshire et al, 2005). The young researchers decided that holding an event would be the best way to speak to children and young people so we decided to hold a fun day.…”
Section: Stage One-identifying Training Needsmentioning
confidence: 99%
“…This study, therefore, is theoretically rooted in a mixed methods approach to inquiry [6] -the surveys are quantitative and the journal reflections are qualitative. It has been argued that using multiple methods is a "valuable approach that does not merely duplicate data but also offers complementary insights and understandings that may be difficult to access through reliance on a single method of data collection" [9].…”
Section: Methodsology and Theoretical Frameworkmentioning
confidence: 99%